The Relationship between Family Resilience, Social Support, and Well-being Families with Disabled Members (A Literature Review) - Sari, Novita; Cholid, Sofyan (Jurnal ORTOPEDAGOGIA, 2024)
This literature review examines the well-being of families in Indonesia raising family with disabilities. By analyzing existing research, the study aims to understand the challenges faced by these families, the support systems available, and the factors influencing their resilience. Key findings highlight the significance of social support, family resilience, and the interplay of parental stress and coping mechanisms in the lives of these caregivers. Additionally, the review explores the impact of different types of disabilities on families and the importance of understanding the unique experiences of each family. The study concludes by emphasizing the need for continued research and support to improve the well-being of families raising children with disabilities in Indonesia and suggests directions for future research.